Implementation of Jkn Capitation Funds at Suranadi Primary Health Center: an Edward III Policy Implementation Analysis - Qatrunnada Emilia Kholidianti; Erliany Syaodih; Rinawati Rinawati (Research of Service Administration Health and Sains Healthys, 2026)
The implementation of capitation financing under Indonesia’s National Health Insurance (Jaminan Kesehatan Nasional/JKN) is intended to strengthen comprehensive primary care, particularly promotive and preventive services. Nevertheless, the translation of capitation policy into daily organizational practice remains uneven across primary health centers. This study analyzes the implementation of JKN capitation funds at Suranadi Primary Health Center, West Lombok, using Edward III’s framework of communication, resources, disposition, and bureaucratic structure. A qualitative case-study design was employed. Data were generated through in-depth semi-structured interviews, non-participant observation, and document review involving the head of the health center, the capitation treasurer, health professionals, and program managers. Data were reduced, coded, categorized, and interpreted thematically, while credibility was strengthened through source and method triangulation, member checking, and an audit trail. The findings demonstrate that implementation has not reached its intended level of effectiveness. Communication remained predominantly one-way, policy information was not evenly distributed, and regulatory changes were not consistently accompanied by operational clarification. Human resources were numerically adequate but unevenly distributed in competence and burden; supporting facilities and integrated information systems were limited; and capitation spending remained oriented toward curative services and service remuneration. Implementers generally accepted the policy, yet commitment was fragmented across administrative, clinical, and program priorities. Although formal structures and standard operating procedures were available, task overlap, weak cross-unit coordination, and centralized decision-making reduced organizational responsiveness. The study concludes that capitation implementation is shaped by the interaction of all four Edward III variables rather than by financial compliance alone. A more effective model requires two-way communication, competency-based workforce development, data-driven and balanced allocation, stronger SOP internalization, integrated digital reporting, and participatory governance.